Not Whodunit But Whydunit: Story Characters' Motivations Influence Audience Interest in Services. (February 2022) - Hamby, Anne; van Laer, Tom
Service providers and consumer well-being advocates often share stories to promote audience interest in relevant behavior. This research examines how characters' motivations for engaging in service-related behavior in such stories influence consumers' interest in services. Across five studies, we show that audiences are more interested in services after reading about a character who acts for intrinsically (vs. extrinsically) motivated reasons. We show that this occurs because the audience identifies more with intrinsically motivated characters. We also examine how consequences of characters' actions (both for others and for themselves when they make miscalibrated decisions) shape an audience's service interest in targeted ways, specifically encouraging interest in services that help people while avoiding unintended negative consequences. The results of this work suggest that stories can be an effective way to encourage consumers' interest in services that enhance personal and societal well-being and identify critical story elements that influence their success in doing so.